2021
DOI: 10.3390/curroncol28050329
|View full text |Cite
|
Sign up to set email alerts
|

CRAFT—A Proposed Framework for Decentralized Clinical Trials Participation in Canada

Abstract: Canada’s vast geography, and centralized delivery of cancer care and clinical trials create barriers for trial participation for patients in remote and rural settings. The development and implementation of a framework that enables safe and regulatory compliant trial participation through local healthcare providers would benefit Canadian patients, clinicians, trial sponsors and the health care system. To address this issue, representatives of Canada’s cancer clinical trial community met to identify key challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 10 publications
2
55
0
Order By: Relevance
“…The adoption of digital health tools to develop and deploy digitally augmented trials has been rising steadily since the first fully remote decentralized trial in 2011 [ 6 - 8 ]. Recent studies have shown the benefits of remote monitoring using smartphones for assessing real-world behavior [ 9 , 10 ], for managing chronic pain [ 11 ], cancer care [ 12 ], diabetes [ 13 ], Parkinson symptom severity [ 14 ], and cardiovascular health [ 15 ] and for the delivery of remote interventions [ 16 ]. The COVID-19 pandemic has further accelerated this growth, enabling over 220 digitally augmented trials in 2021 alone [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of digital health tools to develop and deploy digitally augmented trials has been rising steadily since the first fully remote decentralized trial in 2011 [ 6 - 8 ]. Recent studies have shown the benefits of remote monitoring using smartphones for assessing real-world behavior [ 9 , 10 ], for managing chronic pain [ 11 ], cancer care [ 12 ], diabetes [ 13 ], Parkinson symptom severity [ 14 ], and cardiovascular health [ 15 ] and for the delivery of remote interventions [ 16 ]. The COVID-19 pandemic has further accelerated this growth, enabling over 220 digitally augmented trials in 2021 alone [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A telehealth approach may provide an alternate model to support patients in areas with constraints for intensive in-person cliniciandirected therapy [16]. It also has the potential to improve patient access to cancer care [17] and clinical trials participation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials require institutions with facilities (e.g., clinics, laboratories. pharmacies), infrastructure (e.g., records management systems, financial management systems), and trained research professionals (e.g., physicians, research nurses, clinical trial coordinators, laboratory and radiology technicians, data managers) capable of executing their roles in compliance with regulatory and ethical guidelines [ 11 ]. Health service executive teams also require support and mentoring to implement clinical trial programs.…”
Section: Introductionmentioning
confidence: 99%